Comparative of Pulsatile Index and Resistance Index of Vascularization Intratumoral in Operable and Non Operable Cervical Cancer (Cross Sectional Study) - Harry Kurniawan Gondo (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: A cross sectional study from 49 cases of cervical carcinoma, diagnosed by histopathology, early staged was done by Oncogynecologist at Gyneco-Oncology clinic of Sanglah Hospital. Doppler ultrasonography was used to compared the different Pulsatile Index (PI), Resistance Index (RI) from artery intratumoral with diameter mass of the tumor, including operable and non operable. Method: This research was cross sectional study, present 49 samples established diagnosis with cervical cancer using anatomical patology analyzes and evaluation the staging by the supervisor in the policlinic of Oncology in Sanglah Hospital. Examination of intratumoral vascular cervical cancer Doppler ultrasonography was done at policlinic of Obstetrics Graha Amerta in Sanglah Hospital using Medison instrument, type Sonoace 8000 live prime. The data was analyzed using Kolmogorov Smirnov test normality, then the selected data with Independent Samples Test. Result: Profile mean of age and parity between operable cervical cancer and non operable was not significant (p > 0.05). The mean Pulsatile Index (PI) in operable sample is 0.66 ± 0.9, non operable sample is 1.11 ± 0.84, p=0.089 (p > 0.05), RI for operable sample is 0.32 ± 0.36 and non operable sample is 0.49 ± 0.28 (p > 0.05). Conclusion: There were no significant difference of PI and Resistance Index (RI) between operable and non operable on cervical cancer, but they were different in velocity mean. [Indones J Obstet Gynecol 2010; 34-3: 143-9] Keywords: pulsatile index, resistance index, cervical cancer